(untitled) (International Journal of Physiology, 2020)
Background: Life style modifications like walking, slow deep breathing and dietary modifications play a major role in modifying the components of metabolic syndrome. This study was conducted to determine the effects of non-pharmacological interventions on components of metabolic syndrome among the police personnel in Tirunelveli city. Method: This is a before and after intervention study in which 44 police personnel working in Tirunelveli city in the age group of 30-58 years with metabolic syndrome were included. After getting due permission from the Deputy Commissioner of Police, Tirunelveli and Head of Department of Bio chemistry Department, Institutional Ethical Committee clearance and oral informed consent from the volunteers the study was started. The study was conducted during the period from August to November, 2013. Height, weight, waist circumference, blood pressure estimation and bio-chemical investigations were measured at baseline and 12 weeks after intervention in the study group. Results: It is found that the physiological parameters measured before and after non pharmacological intervention in the study group indicate a distinct and statistically significant reduction in all the values and a significant increase in HDL. Recommendation: Physical fitness schedule, along with stress alleviation techniques and dietary modifications may be made mandatory to keep the police personnel physically and mentally healthy.